2022
DOI: 10.1097/prs.0000000000009861
|View full text |Cite
|
Sign up to set email alerts
|

Orthoplastic Treatment of Open Lower-Limb Fractures Improves Outcomes: A 12-Year Review

Abstract: Background: The British Orthopaedic Association Standards for Orthopaedics and Trauma 4 (BOAST 4) inform the management of open lower-limb fractures. The authors conducted repeated reviews of performance against these standards over a 12-year period. This latest iteration has shown further improvements in outcomes concomitant with changes in service delivery. Methods: Data on Gustilo-Anderson grade IIIB or IIIC open lower-limb fractures were collected from a prospectively constructed departmental database an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…In the United Kingdom (UK) treatment structures have already been put in place to provide adequate and timely care to patients with these kinds of injuries. The British Orthopedic Association (BOA) and the British Association of Plastic, Reconstructive and Aesthetic Surgeons (BAPRAS) introduced evidence-based standards of care for the treatment of severe, open lower leg fractures (BOAST) [15]. It has been demonstrated that an early transfer of patients to specialized trauma centers and cooperation between surgical and non-surgical disciplines significantly improve the course of treatment.…”
Section: Original Manuscriptmentioning
confidence: 99%
“…In the United Kingdom (UK) treatment structures have already been put in place to provide adequate and timely care to patients with these kinds of injuries. The British Orthopedic Association (BOA) and the British Association of Plastic, Reconstructive and Aesthetic Surgeons (BAPRAS) introduced evidence-based standards of care for the treatment of severe, open lower leg fractures (BOAST) [15]. It has been demonstrated that an early transfer of patients to specialized trauma centers and cooperation between surgical and non-surgical disciplines significantly improve the course of treatment.…”
Section: Original Manuscriptmentioning
confidence: 99%